2011
DOI: 10.1021/la200982n
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Superhydrophobic Microspheres of Poly(vinylidene fluoride– hexafluoropropylene)/Graphene Composite via Gelation

Abstract: We report on the spontaneous formation of superhydrophobic poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP)/graphene composite microspheres with uniform size via gelation. When the suspension of PVDF-HFP/graphene (0.25 wt. % with respect to PVDF-HFP) in DMF adsorbs water vapor, it changes to a hybrid gel. A dried porous gel is obtained after solvent exchange and freeze drying. Morphology characterization shows that this hybrid gel is composed of PVDF-HFP/graphene microspheres with a diameter of 8-10 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…al., for instance; reported that acetone or molecular water attaching to the surface of graphene can change its wettability to superhydrophilic [20]. In addition, there are several reports that have tried to enhanced wettabilty of graphene based composites [21][22][23][24]. Although it is known that functional groups such as hydroxyl and carboxyl are hydrophilic however, due to the presence of various functional groups on the GO surface, the main hydrophilic functional group is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…al., for instance; reported that acetone or molecular water attaching to the surface of graphene can change its wettability to superhydrophilic [20]. In addition, there are several reports that have tried to enhanced wettabilty of graphene based composites [21][22][23][24]. Although it is known that functional groups such as hydroxyl and carboxyl are hydrophilic however, due to the presence of various functional groups on the GO surface, the main hydrophilic functional group is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…With addition of 1 wt% graphite powder, the melting temperature of dried PVDF composite increased slightly. 63 However, dry PVDF composite samples showed a widening peak compared to pure PVDF samples, and this is illustrated in the cooling curves.…”
Section: The Effect Of Graphitementioning
confidence: 97%
“…3, fluorinated polymers are commonly used as low surface energy materials; for example, polyvinylidene fluoride (PVDF) is used to produce superhydrophobic materials [134][135][136]. Zha et al [135] demonstrated a combined method of solvent exchanging and freeze-drying to fabricate PVDF porous materials that can effectively avoid the skin-layer formation of dried materials.…”
Section: Superhydrophobicity On Cntsmentioning
confidence: 99%
“…Several experimental and modeling studies have focused on exploiting micro-scale surface roughness to engineer superhydrophobic graphene. Several research groups have fabricated superhydrophobic graphene surfaces using an irregular stack of graphene oxides (GO) prepared by chemical oxidation of graphite, and pertinent results are shown in Table 2 [131][132][133][134][135][136][137][138][139][140][141][142][143][144]. blocks to create a superhydrophobic structure with an ordered pore structure of ~200 μm in dimension.…”
Section: Superhydrophobicity On Graphenementioning
confidence: 99%
See 1 more Smart Citation